Effects of heat removal through the hand on metabolism and performance during cycling exercise in the heat - Hsu, A. R.; Hagobian, T. A.; Jacobs, K. A.; Attallah, H.; Friedlander, A. L. (Canadian Journal of Applied Physiology, 2005)
Objective: This two-part study tested the hypotheses that the use of a new cooling device, purported to extract heat from the body core through the palm of the hand, would (a) attenuate core temperature rise during submaximal exercise in the heat, thereby suppressing exercise-associated metabolic changes, and (b) facilitate a higher sustained workload, thus shortening the completion time of a time-trial performance test. Methods: In Study 1, 8 male triathletes (age 27.9 ± 2.0 yrs, mass 77.2 ± 3.1 kg, VO2peak 59.0 ± 4.1 ml·min-1·kg-1) cycled for 1 hr at the same absolute workload (~60% VO2peak) in a heated room (31.9 ± 0.1 °C, 24 ± 1% humidity) on two occasions counterbalanced for cooling (C) or noncooling (NC). In Study 2, 8 similar subjects (age 26.9 ± 2.0 yrs, mass 75.2 ± 3.7 kg, VO2peak 54.1±3.1 ml·min-1·kg-1) performed two 30-km cycling time-trial performance tests under the same conditions (CT, NCT). Results: In Study 1, cooling attenuated the rise in tympanic temperature (TTY) (1.2 ± 0.2 vs. 1.8 ± 0.2 °C; p < 0.01) and lowered mean oxygen consumption (V .O2, 2.4 ± 0.1 vs. 2.7 ± 0.1 L·min-1; p < 0.05) and blood lactate (1.7 ± 0.2 vs. 2.2 ± 0.2 mmol·L-1; p < 0.01) during exercise. There were no significant differences in respiratory exchange ratio (RER), blood glucose, heart rate (HR), face temperature (TF), or back temperature (TB) between NC and C. In Study 2, time to complete 30 km was 6 ± 1% less with cooling than without cooling (60.9 ± 2.0 vs. 64.9 ± 2.6 min; p < 0.01). During the last 20% of CT, subjects sustained a workload that was 14 ± 5% (p = 0.06) higher than NCT at the same TTY and HR. Conclusions: Heat extraction through the hand during cycle ergometer exercise in the heat can (a) lower TTY, lactate concentration, and V . O2 during a submaximal set-workload test and (b) reduce the time it takes to complete a 30-km time-trial test.